2020
DOI: 10.2340/16501977-2709
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the structural validity of three Balance Evaluation Systems Test in older adults with femoral or vertebral fracture

Abstract: The Balance Evaluation Systems Test (BESTest), a clinical balance measure, categorizes balance into 6 factors. The aim of this study was to determine which short versions of the BESTest, Mini-BESTest, and Brief-BESTest, were most appropriate for assessing balance impairments in older adults with femoral or vertebral fracture. Subjects were older adults (age ≥65 years), who could walk with out physical assistance. The models' fitting was evaluated for four BESTest models (BESTest, one-factor Mini-BESTest, four-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 30 publications
1
7
2
Order By: Relevance
“…Our additional analysis suggested that the same measure may have different characteristics depending on the disease. Despite the effect of sample size, the background diseases and symptoms were different between Franchignoni et al's series study (1,(3)(4)(5)(6)9) and the present study (2). Balance is a complex ability that involves rapid, automatic, anticipatory, reactive integration, and sensory strategies, and its properties should differ between age-related functional decline and balance disturbances with neurological symptoms.…”
Section: Response To Letter To the Editor From Franco Franchignoni Ancontrasting
confidence: 70%
See 1 more Smart Citation
“…Our additional analysis suggested that the same measure may have different characteristics depending on the disease. Despite the effect of sample size, the background diseases and symptoms were different between Franchignoni et al's series study (1,(3)(4)(5)(6)9) and the present study (2). Balance is a complex ability that involves rapid, automatic, anticipatory, reactive integration, and sensory strategies, and its properties should differ between age-related functional decline and balance disturbances with neurological symptoms.…”
Section: Response To Letter To the Editor From Franco Franchignoni Ancontrasting
confidence: 70%
“…We thank Franchignoni and Giordano for their insightful comments (1) on our article (2). As their comments suggest, our study has problems regarding generalization based on the sample size, subject characteristics (i.e.…”
Section: Response To Letter To the Editor From Franco Franchignoni Anmentioning
confidence: 97%
“…For this latter scale, structural analysis points toward the presence of (still not clearly defined) multidimensionality. 32,33 Rasch analysis confirmed the correct functioning of the 3 response categories of the Mini-BESTest (ie, they could distinguish distinct levels of balance ability) and thus their adequateness for contributing to a good measurement quality. 21 All items showed good fit to the Rasch model, that is, appropriateness of the scale's items for measuring the latent construct of interest (dynamic balance).…”
Section: Discussionmentioning
confidence: 72%
“…On the other hand, the Mini-BESTest unidimensionality precludes proposing any separate subscore17,33 based on the postural control systems postulated in BESTest. For this latter scale, structural analysis points toward the presence of (still not clearly defined) multidimensionality 32,33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation